2012
DOI: 10.1073/pnas.1202439109
|View full text |Cite
|
Sign up to set email alerts
|

TCP transcription factor, BRANCH ANGLE DEFECTIVE 1 (BAD1), is required for normal tassel branch angle formation in maize

Abstract: In grass inflorescences, a structure called the "pulvinus" is found between the inflorescence main stem and lateral branches. The size of the pulvinus affects the angle of the lateral branches that emerge from the main axis and therefore has a large impact on inflorescence architecture. Through EMS mutagenesis we have identified three complementation groups of recessive mutants in maize having defects in pulvinus formation. All mutants showed extremely acute tassel branch angles accompanied by a significant re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
97
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 101 publications
(105 citation statements)
references
References 24 publications
8
97
0
Order By: Relevance
“… Phylogenetic tree of plant species in which TCP transcription factors are involved in branching (Takeda et al, 2003; Aguilar-Martínez et al, 2007; Poza-Carrión et al, 2007; Bai et al, 2012; Braun et al, 2012; Drummond et al, 2015; Nicolas et al, 2015; Muhr et al, 2016) (blue dots), flower development (Linnaeus and Rudberg, 1744; Keeble et al, 1910; Corley et al, 2005; Costa et al, 2005; Busch and Zachgo, 2007; Broholm et al, 2008; Kim et al, 2008; Nag et al, 2009; Yuan et al, 2009; Howarth et al, 2011; Busch et al, 2012; Tähtiharju et al, 2012; Claßen-Bockhoff et al, 2013; Juntheikki-Palovaara et al, 2014; De Paolo et al, 2015; Horn et al, 2015; Lucero et al, 2015; Wang et al, 2008; Wang X.et al, 2015; Yang et al, 2015; Berger et al, 2016) (purple dots) or leaf development (Kosugi and Ohashi, 1997; Nath et al, 2003; Palatnik et al, 2003; Koyama et al, 2007, 2010a,b; Ori et al, 2007; Efroni et al, 2008; Kieffer et al, 2011; Mimida et al, 2011; Sarvepalli and Nath, 2011; Danisman et al, 2012, 2013; Aguilar-Martínez and Sinha, 2013; Burko et al, 2013; Tao et al, 2013; Zhou et al, 2013; Ballester et al, 2015; Huang and Irish, 2015; Ma et al, 2016) (green dots), respectively. The phylogenetic tree was created using Phylotree and iTOL (Letunic and Bork, 2016).…”
Section: Evolutionary Conserved Roles Of Tcpsmentioning
confidence: 99%
“… Phylogenetic tree of plant species in which TCP transcription factors are involved in branching (Takeda et al, 2003; Aguilar-Martínez et al, 2007; Poza-Carrión et al, 2007; Bai et al, 2012; Braun et al, 2012; Drummond et al, 2015; Nicolas et al, 2015; Muhr et al, 2016) (blue dots), flower development (Linnaeus and Rudberg, 1744; Keeble et al, 1910; Corley et al, 2005; Costa et al, 2005; Busch and Zachgo, 2007; Broholm et al, 2008; Kim et al, 2008; Nag et al, 2009; Yuan et al, 2009; Howarth et al, 2011; Busch et al, 2012; Tähtiharju et al, 2012; Claßen-Bockhoff et al, 2013; Juntheikki-Palovaara et al, 2014; De Paolo et al, 2015; Horn et al, 2015; Lucero et al, 2015; Wang et al, 2008; Wang X.et al, 2015; Yang et al, 2015; Berger et al, 2016) (purple dots) or leaf development (Kosugi and Ohashi, 1997; Nath et al, 2003; Palatnik et al, 2003; Koyama et al, 2007, 2010a,b; Ori et al, 2007; Efroni et al, 2008; Kieffer et al, 2011; Mimida et al, 2011; Sarvepalli and Nath, 2011; Danisman et al, 2012, 2013; Aguilar-Martínez and Sinha, 2013; Burko et al, 2013; Tao et al, 2013; Zhou et al, 2013; Ballester et al, 2015; Huang and Irish, 2015; Ma et al, 2016) (green dots), respectively. The phylogenetic tree was created using Phylotree and iTOL (Letunic and Bork, 2016).…”
Section: Evolutionary Conserved Roles Of Tcpsmentioning
confidence: 99%
“…In Commelina (Commelinales) and the Zingiberales, there is some evidence for a correlation between CYC-like gene expression and the development of floral zygomorphy (Bartlett and Specht, 2011;Preston and Hileman, 2012). Functional studies of the CYC-like genes in the grasses implicate them in the control of shoot branching (Doebley et al, 1995;Kebrom et al, 2006), inflorescence branch angle and leaf morphology (Bai et al, 2012), and lemma versus palea identity in rice (Yuan et al, 2009), not structural floral zygomorphy. In a number of orchids, the development of distinct second and third whorl tepals associated with zygomorphy is associated with variability in AP3/DEF homolog expression and variability in floral MADS box complex formation (Mondragón-Palomino and Theissen, 2008Theissen, , 2011Hsu et al, 2015).…”
Section: Maize Floral Zygomorphy and B Class Functionmentioning
confidence: 99%
“…4E,F). lg1 regulates leaf architecture (Moreno et al 1997;Tian et al 2011), and loss-of-function lg1 mutants display upright tassel branches (Bai et al 2012). Although a branch number phenotype has not been reported for lg1 mutants, a recent genome-wide association study identified lg1 as a candidate locus controlling tassel branch number ).…”
Section: Figurementioning
confidence: 99%